Political discourse in the media : cross-cultural perspectives - Fetzer, Anita, 1958-; Lauerbach, Gerda (Pragmatics & beyond, 2007)
This book departs from the premise that political discourse is intrinsically connected with media discourse, as shaped by its cultural and transcultural characteristics. It presents a collection of papers which examine political discourse in the media from a cross-culturally comparative perspective in Arab, Dutch, British, Finnish, Flemish, French, German, Israeli, Swedish, US-American and international contexts. By using different theoretical frameworks, such as conversation analysis, discourse analysis, pragmatics and systemic functional linguistics, the papers reflect current moves in polit.